Developed Methodology for Ship Retrofitting (Case Study: RV Baruna Jaya I) - Dwitya Harits Waskito; Ahmad Muhtadi; Tris Handoyo; Rio Dwi Sakti Wijaya; Prastya Rizky Ramadhan (Department of Naval Architecture - Diponegoro University, 2023)
Ship retrofitting is one alternative solution to extend a ship’s life. Several component replacements were performed in the retrofitting process, remodelings to the ship’s main dimension, and state-of-the-art equipment and technology were added. As one of the ships that require regular renewal, especially in research equipment, retrofit processes are often carried out on research vessels. The current problem in the retrofit process for research vessels, especially in Indonesia, is that retrofits are not carried out with established methodology and planning. Thus, some retrofit projects are limited to major repairs and do not extend the ship’s life or performance. To solve that problem, a developed methodology for ship retrofitting was proposed, which consists of selecting the ship and the type of retrofit and its components, determining retrofit requirements, and designing the ship based on the retrofit project. In the design process, a modified spiral design is explicitly used for the retrofit process with some alterations compared with the conventional one, which is focused on analyzing the suitability and availability of space, consumable and tank requirements, analysis of power requirements, risk analysis, and project execution plan. A case study of this developed methodology has been undertaken in the concept design phase of RV Baruna Jaya 1’s retrofit, and the results show that the methodology is considered helpful as an approach for ship retrofitting. Moreover, several considerations were also obtained from the concept design stage and had to be analyzed at the following design stage to meet the retrofit design requirements.